Isothermal section of the Gd-Mn-Ge ternary system at 1070 K - Konyk, M.; Romaka, L.; Romaka, V.V.; Stadnyk, Yu. (Physics and Chemistry of Solid State, 2025)
Interaction between the components in the Gd–Mn–Ge ternary system was studied at 1070 K over the whole concentration range using scanning electron microscopy, energy dispersive X-ray microanalysis and X-ray diffractometry. At 1070 K Gd–Mn–Ge system is characterized by existence of six ternary compounds: GdMn4Ge2 (ZrFe4Si2 structure type, space group P42/mnm, a = 0.7645(4) nm, c=0.3953(3) nm), GdMnGe (TiNiSi structure type, space group Pnma, a=0.7129(2), b=0.4166(2), c=0.8201(2) nm), Gd3Mn4Ge4 (Gd3Cu4Ge4 structure type, space group Immm, a=1.4023(4), b=0.7121(3), c=0.4212(3) nm), GdMn2Ge2 (CeAl2Ga2 structure type, space group I4/mmm, a=0.40326(6), c=1.0884(2) nm), GdMn6Ge6 (MgFe6Ge6 structure type, space group P6/mmm, a = 0.52377(5), c = 0.8182(1) nm) and GdMn1-хGe2 (CeNiSi2 structure type, space group Cmcm, a = 0.41612(8)-0.41590(7), b = 1.6123(3)-1.6119(1), c = 0.40336(8)-0.40290(6) nm). For the GdMn1-хGe2 compound the homogeneity range was determined (x=0.70-0.64).